TEN YEARS OF RETROSPECTIVE PROFILING OF THE ABANDONED FETUSES AND NEWBORNS - SINGH, JASPINDER PRATAP; KUMAR, KULDIP; SHARMA, AASHISH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Despite the problem being present in every corner of our country, research studies are scarce on the topic of the abandonment of fetuses or newborns. In this light, this research seeks to look at the prevalence and autopsy profiling into the cases of abandonment of newborns/fetuses and the possible suggestions. Methods: The present 10 years prospective study was conducted to observe the profiling of the abandoned newborns/fetuses after taking permission from the institutional ethical committee. The records of all the medico-legal autopsies conducted under 317 IPC at Government Medical College, Amritsar, from January 2014 to February 2023, were analyzed. Results: The total number of autopsy cases conducted under 317 IPC. In the present study, 02 (9.1%) females were known cases, while among the unknown cases, there 06 (27.3%) were males and 14 (63.6%) were female. Most cases were females, 16 (72.7%) and 6 (27.3%) were males. The maximum number of cases reported in 2019 was 4 (18.2%), while 03 (13.6%) were reported in 2016 and 2021, respectively. The most common were homicidal deaths in 14 (63.6%) cases, followed by natural deaths in 5 (22.7%) cases, and the cause of death could not be ascertained in 3 (13.7%) cases. Conclusion: Whatever the reason or motive for the newborn or fetuses’ abandonment, this issue needs urgent attention.